Anti-glycine receptor antibody-positive progressive encephalomyelitis with rigidity and myoclonus initially presenting with one-sided stiff face: A case report - Irie, Ken-Ichi; Tateishi, Takahisa; Moritaka, Taiga; Sakurada, Naonori; Kikuchi, Shinsuke; Taniwaki, Takayuki (Frontiers in Neurology, 2022)
Background Progressive encephalomyelitis with rigidity and myoclonus (PERM) is a subtype of stiff-person syndrome, a rare cerebrospinal disease that causes brainstem symptoms, myoclonus, muscle rigidity, and hyperekplexia. Case presentation A 71-year-old man experienced left-sided stiff face, and was subsequently admitted to our hospital because of the appearance of left-dominant lower limb myoclonus. Muscle rigidity followed 3 days later. Magnetic resonance imaging revealed no abnormality. An electrophysiological examination showed a toughness of the antagonistic muscle following evocation of the Achilles tendon reflex, and a tonic phenomenon affecting the left facial muscles during the blink reflex. The patient's serum was positive for anti-glycine receptor (anti-GlyR) antibody, suggesting PERM. The patient was administered steroids, immunoglobulin therapy, and immunosuppressive drugs. He gradually improved after these therapies and became able to walk using a walker. Conclusions We conclude that this was a rare case of anti-GlyR antibody-positive PERM with unilateral brainstem symptoms, myoclonus, and muscle rigidity.